Bridging Entrepreneurial and Digital Marketing to Enhance Business Performance: The Mediating Role of Innovation Capability and the Moderating Role of Gender - Padmawidjaja, Liestya; Rokhman, M Taufiq Noor; Mitasari, Alodia Rean (Universitas Brawijaya, Indonesia, 2025)
The economic expansion of Surabaya is primarily driven by trade, lodging, and food and beverage services. At the same time, the culinary micro, small, and medium enterprises (MSMEs) experience some hardships when it comes to increasing their business performance, such as being unable to obtain formal bank credit because of their ‘unbankable’ status, which makes it hard to estimate profit margins, and declining business performance. The purpose of this study is to investigate how entrepreneurial marketing and digital marketing increase business performance, with innovation capability as a mediator. The study used a quantitative approach, and the sample consisted of 170 culinary MSME (Micro, Small, and Medium Enterprise) owners in Surabaya. Through the application of Structural Equation Modeling (SEM) with the PLS technique, the findings show that both entrepreneurial marketing and digital marketing have a substantial impact on innovation capability and business performance. On the other hand, innovation capability fails to mediate the relationship between entrepreneurial marketing and business performance, while it effectively mediates the influence of digital marketing on the business performance of culinary MSMEs in Surabaya. Moreover, gender does not play a role in the effect of either entrepreneurial marketing or digital marketing on a business's performance. Surabaya's culinary MSMEs need to hone their customer intensity skills by identifying and learning about the customers' tastes, pricing expectations, and even engaging the consumers through feedback sessions on new menus, packaging, or promotional ideas. Moreover, the adoption of more informative digital marketing practices by the MSMEs could facilitate the understanding of the customer's preferences.